2004
DOI: 10.1007/s00340-003-1400-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase-matched enhancements of high-harmonic soft X-rays by adaptive wave-front control with a genetic algorithm

Abstract: We demonstrate the enhancement of high-harmonic soft-X-ray generation by adaptive wave-front control of a 745-nm Ti:sapphire laser by use of a 59-channel membrane deformable mirror, combined with a genetic algorithm, for the first time to our knowledge. The harmonics ranging from 17 nm to 28 nm were enhanced by factors up to 13. The numerical calculations illustrate that the enhancements of the plateau harmonics are due to macroscopic phase-matching effect, whereas those of the cutoff harmonics are due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…DMs have been used in the past to modify the wavefront of the driving beam for HHG in setups with high repetition rates. This has been done to modify the astigmatism in the harmonic wavefront [29], and also to improve phase matching and thus the energy in the resulting APTs [43].…”
Section: Using Ir Adaptive Optics To Improve the Xuv Wavefrontsmentioning
confidence: 99%
“…DMs have been used in the past to modify the wavefront of the driving beam for HHG in setups with high repetition rates. This has been done to modify the astigmatism in the harmonic wavefront [29], and also to improve phase matching and thus the energy in the resulting APTs [43].…”
Section: Using Ir Adaptive Optics To Improve the Xuv Wavefrontsmentioning
confidence: 99%
“…transmission of quantum information from one standing qubit to another via a flying photon qubit [41]) or field-field interaction (e.g. soft X-ray generation from a visible laser source [42]). In this regard, we will start from the description of matter-field interactions, showing that a control model with inputs and outputs can be built up by tuning either the fields or the material structures.…”
Section: Introductionmentioning
confidence: 99%
“…In a general sense, spatial shaping of the beam can be exploited to achieve both operations. Studies have been reported, using an annular slit in the beam [41], a hollow fiber [42], an adaptive mirror [43][44][45], or a Bessel-Gauss beam [46,47].…”
Section: Introductionmentioning
confidence: 99%